PRODUCTION AND UTILIZATION OF RUBBER WOOD IN THAILAND: II. WOOD UTILIZATION AND ECONOMIC ASPECTS - Urapeepatanapong, Chavalit (วารสารวนศาสตร์ไทย, 2022)
Utilization trends of rubber wood in Thailand were increased from 1. 48 million m³ in 1976 to 2.55 million m³ in 1979 and 3.04 million m3 in 1982. The current survey in 1987 showed that there were 4.53 million m³ of stack volume equivalent to 3.05 million m3 of solid volume being utilized, i.e., 30.43% as fuelwood, 11.02% as charcoal, 16.68% as particleboard, 1.83% as pole and pile, and 40.04% as furniture and other wood products. The amounts of wood utilized (4.53 million m³/yr) accounted for 42.25% of total wood wood produced (10.72 million m³/yr), while the remaining 57.75% was leftover at the plantation sites. Prices of rubber wood varied with types of using, size, quality, and locality. Normally, average purchasing price in the East was at least two times higher than in the South. Besides domestic consumption, sawn rubber wood was exported to Japan, Taiwan, and Korea at the FOB price of 18,758 baht/m³ for superior lumber for furniture making. The export volumes were increased from 1,696 m³ in 1984 to 58,820 m³ in 1987. Problems and factors limiting rubber wood utilization were discussed.